Perancangan Identitas Visual dan Media Sosial Instagram sebagai Sarana Branding pada Cahya Musik Wedding Organizer - Eka Rimbaniasari; Irdha Yunianto (Lembaga Pengembangan Kinerja Dosen, 2026)
The wedding organizer industry in Indonesia has experienced rapid growth alongside the increasing public demand for professional and integrated wedding services. Intensifying competition has encouraged businesses to establish strong brand identities through visual branding and the effective use of social media. This study aims to design an integrated visual identity and Instagram content strategy to enhance the brand awareness and engagement of Cahya Musik Wedding Organizer. The research employed a qualitative approach using the practice-based research method and the Design Thinking process, consisting of empathize, define, ideate, prototype, and test. Data were collected through Instagram account observation, in-depth interviews, documentation, and a literature review. The findings revealed that the existing branding lacked visual consistency and had a relatively low engagement rate of 2.1%. The newly developed visual identity established a consistent branding system through a logo incorporating musical notation and wedding ring elements, an elegant color palette, representative typography, and Instagram content templates based on visual storytelling. The implementation increased the engagement rate to 6.8%, representing a 224% improvement, accompanied by higher numbers of likes, comments, shares, and saves. These findings demonstrate that integrating a consistent visual identity with a well-structured Instagram content strategy is effective in improving brand awareness, engagement, and the competitive positioning of Cahya Musik Wedding Organizer in the wedding services industry.